Risk Predictors for Mortality in Inpatients with Cancer and Coronavirus Disease 2019 during the Omicron Wave - Kuan-Yu Chen; Chih-Cheng Lai; Chien-Tai Huang; Yin-Hsun Feng (Journal of Cancer Research and Practice)
Background: Patients with cancer are a high-risk population in the coronavirus disease 2019 (COVID-19) pandemic. We analyzed the characteristics and risk factors for mortality in hospitalized patients with cancer and laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during the Omicron wave. Materials and Methods: We conducted a retrospective, single-center, cohort study of 206 patients with cancer and SARS-CoV-2 infection in southern Taiwan. Clinical characteristics, laboratory data, and cancer characteristics were compared between survivors and nonsurvivors. Risk factors for mortality were identified by univariable and multivariable logistic regression models. Results: The median patient age was 69.5 years. Male preponderance was noted (65%). Comorbidities were present in 186 (90%) cases. A total of 113 (54%) patients had active cancer. Metastatic disease accounted for 78 (38%) cases, of whom 19 (9%) had lung metastasis. Sixty-four (31%) patients had active and progressing cancer status. The overall inhospital mortality rate was 17.4%. Univariate logistic regression revealed the following factors to be significantly associated with a higher risk of inhospital mortality among the patients with cancer and COVID-19: nosocomial COVID-19 infection (P = 0.037), lung metastasis (P = 0.005), received anticancer therapy in the preceding 3 months (P = 0.083), active and progressing cancer (P = 0.008), and quick Sequential Organ Function Assessment (qSOFA) score ≥2 (P < 0.001). However, only nosocomial infection (P = 0.021) and qSOFA score ≥2 (P < 0.001) were independent predictors of inhospital mortality in the multivariate logistic regression analysis. Conclusion: Cancer patients are a population vulnerable to the Omicron variant with higher mortality rate, especially those with nosocomial COVID-19 infection and those with a qSOFA score of ≥2 immediately after confirmation of COVID-19 infection. Thus, the rapid recognition of high-risk groups and nosocomial infection control are critical to prevent COVID-19 in patients with cancer.